KUALITAS PELAYANAN PENGURUSAN DOKUMEN KEPENDUDUKAN DI KANTOR KECAMATAN PALU BARAT KOTA PALU - Elam, Hasnah (Katalogis, 2016)
This study aimed to analyze the quality and the influencing factors of population documents service at the Office of West Palu District Palu City. Informants in this study were amounted to 6 people, consisting of four employees and two people. The informant determination technique used was purposive sampling, namely selecting or choosing informants, interviews, and documentations. The results showed that the quality of population documents service at the Office of West Palu District Palu City had not been done well. This was evidenced that only two of the five indicators used as benchmarks in this study which were met well, namely the responsiveness indicator which indicated that the District apparatuses had been providing responsiveness to the people when experiencing difficulties in the processing of a populations document, and the empathy indicator which indicated that the District apparatuses had treated the people fairly. While the assurance, physical evidence, and reliability indicators were in the category of less than maximum. The assurance indicator, which has knowledge aspect, showed that just only one of the two employees providing the population documents service who had attended training. The physical evidence indicators, which has there aspectÂ  supporting facilities, state of the reception area and tidiness of apparatuses,Â  had not been implemented in accordance with the expectations. The reliability indicator, which has time appointment accuracy aspect, the population documents resolution time was not in accordance withthe time promised. Â